Origins of Carbon Dust in a JWST-observed Primeval Galaxy at z ∼ 6.7 - Ambra Nanni; Michael Romano; Darko Donevski; Joris Witstok; Irene Shivaei; Michel Fioc; Prasad Sawant (The Astrophysical Journal Letters, 2025)
JADES-GS-z6-0, a high-redshift galaxy ( z  ∼ 6.7) recently observed as part of the James Webb Space Telescope Advanced Deep Extragalactic Survey (JADES), exhibits a distinct bump in its rest-frame ultraviolet (UV) spectrum indicative of a large quantity of hydrocarbon grains, a sign of rapid metal and dust enrichment in its interstellar medium (ISM). This galaxy serves as an ideal case for examining rapid dust formation processes in the early Universe. We investigated diverse dust production channels from a possible maximal formation redshift of z _form  ≈ 17, enabling dust contributions from asymptotic giant branch (AGB) stars over the longest possible timescale. Our model simultaneously reproduces key spectral features of JADES-GS-z6-0 such as its Balmer decrement, UV slope, and UV bump. The match is obtained by adopting a star formation history in which a burst at ∼600 Myr accounts for approximately 30% of the galaxy’s final stellar mass. Our findings indicate two pathways for the formation of hydrocarbon grains, such as polycyclic aromatic hydrocarbons (PAHs): (1) efficient dust accretion within the ISM, necessitating a low depletion of metals into dust grains from Type II supernovae (≈10%), or (2) dust production predominantly by Type II supernovae, requiring a high depletion fraction (≈73%) without dust accretion. We further demonstrate that PAHs are unlikely to originate solely from AGB stars or from shattering of large grains in the ISM. The evolution of the UV slope with redshift points to a complex and bursty star formation history for galaxies observed by JADES.